Theoretical and experimental investigation on heat pipe solar collector integrated with latent heat thermal energy storage / Mohammad Sajad Naghavi Sanjani - Mohammad Sajad , Naghavi Sanjani (2016)
The purpose of this research is to evaluate theoretically and experimentally the thermal performance of a compact design of an evacuated tube heat pipe solar collector integrated with a latent heat storage tank. Paraffin wax is used as phase change material in the latent heat storage tank. In this design, solar energy incident on the solar tubes is collected and stored in the latent heat storage tank via the heat pipe with fins attached to the condenser ends inside the latent heat storage tank. The stored heat is then transferred to the supply water via a set of finned pipes located inside the tank. The phase change material acts as an intermediate heat storage medium between the solar collector and the hot water supply. This design is studied in two steps. Primarily, the simplified design of the proposed system is theoretically modeled by applying sets of mathematical equations to have a basic estimation on the performance of the system. Then, after preparing the technical design of the system and constructing the experimental setup in the actual size, the field tests are carried out in two cases. First, is for charging only and discharging only modes and second, is for simultaneous charging-discharging mode. The significances of this design could be expected in three cases. First, the prevention of overheating of the supplied water at times that the solar radiation is very strong and second is extending the performing time of the system in the evening when the system is on second mode. Third, to increase the absorbed solar energy fraction. The results of the primary analysis show that for a large range of flow rates, the thermal performance of this design is higher than of a similar system without latent heat storage. Furthermore, the analysis shows that the efficiency of the new design is less sensitive to the hot water load than the conventional model. The field tests of the experimental setup are taken for different weather conditions, supply water flow rates and hot water draw off time. The results indicated that this design is able to perform satisfactorily in different climatic condition and water flow rates. In addition, this design makes the solar water heater system able to collect the heat at the midday time with highest solar radiation intensity and deliver it to the supply water at the same time or hours later, while the outlet hot water is in the operating temperature range. According to the experimental results, depending on the daily solar radiation, the efficiency of the system varies in the range of 36% to 42%. Daily solar radiation and hot water load are directly proportional to the efficiency of the system. The experimental tests for simultaneous charging-discharging indicated that the system is able to produce hot water in day time and night time for domestic use in a tropic climatic region like Malaysia. Generally, it could be concluded that this design is suitable for use as a stand-alone system for hot water demands at night as part of a configuration with conventional solar water heater systems to produce hot water in duration of day and night for different patterns of hot water demand.